Spillover Benefits: Emphasizing Different Benefits of Environmental Behavior and Its Effects on Spillover - Van Der Werff, Ellen; Steg, Linda (Frontiers in Psychology, 2018)
To reduce environmental problems, people need to consistently engage in pro-environmental behaviours. Many environmentally-friendly actions not only benefit the environment, but can also save money. Research suggests that emphasizing monetary benefits of pro-environmental behaviour may hinder positive spillover to other pro-environmental behaviours. Yet, it is unclear why and under which circumstances this is the case. We propose that spillover effects depend on how emphasizing different types of benefits affects environmental self-identity, as a stronger environmental self-identity is more likely to lead to other pro-environmental actions. We hypothesize that emphasizing monetary benefits of pro-environmental behaviour is less likely to strengthen environmental self-identity than emphasizing environmental benefits, and therefore not likely to lead to positive spillover. We tested our hypotheses in four experiments. In Study 1 we found that emphasizing the environmental benefits of pro-environmental behaviour strengthened environmental self-identity, and resulted in positive spillover compared to not emphasizing any benefits or emphasizing monetary benefits. However, these results were not replicated in Study 2 that included a larger student sample. Yet, Study 3, including a large sample of the general population, showed that emphasizing monetary benefits weakens environmental self-identity and thereby leads to less spillover than emphasizing environmental benefits or not emphasizing any benefits. Similarly, Study 4 suggests that emphasizing monetary benefits may weaken environmental self-identity and decrease positive spillover compared to emphasizing environmental benefits or no benefits. Our findings suggest that environmental self-identity is not easily influenced by emphasising different types of benefits of behaviour, and consequently, spillover behaviour is not easily promoted or inhibited. Yet, emphasizing monetary benefits may be a risk in some cases, as it may inhibit positive spillover.